Novel Control Methods for Phase Lock Loops - Röber, Jürgen; Zwick, Christian; Bänisch, Andreas; Dirauf, Simon; Roppenecker, Günter; Weigel, Robert; Dirauf, Simon (European conference on circuit theory and design (ECCTD), 2015)
This paper discusses different approaches to improve the settling behavior of phase lock loops (PLL). Starting with a state-of-the-art PLL, a structure with an additional dynamic changing Loop-Filter and another structure with feed forward control are proposed. The main point of this paper is the adaption of modern control theory in the design of PLL systems to improve the behavior in case of a changing dividing factor and thereby the output frequency. For both structures, advantages and disadvantages are discussed and then the block diagram of the two approaches are presented. Both methods are compared to the state-of-the-art by simulations in MatLab Simulink. Therefore a massive changing output frequency of the PLL and the corresponding time for locking to the new output frequency is analyzed. All in all both novel PLL concepts offer a reduced settling time with respect to a specified change of the PLL output frequency.
elib2cris::1512001600,roeber2015a
Keywords: PLL; Phase Lock Loop; Synthesizer; Control Theory; Behavioral Modeling